2017
DOI: 10.1073/pnas.1619665114
|View full text |Cite
|
Sign up to set email alerts
|

Guanylate-binding protein 1 (GBP1) contributes to the immunity of human mesenchymal stromal cells against Toxoplasma gondii

Abstract: Mesenchymal stromal cells (MSCs) have recently been shown to play important roles in mammalian host defenses against intracellular pathogens, but the molecular mechanism still needs to be clarified. We confirmed that human MSCs (hMSCs) prestimulated with IFN-γ showed a significant and dose-dependent ability to inhibit the growth of two types of Toxoplasma gondii [type I RH strain with green fluorescent proteins (RH/GFP) or type II PLK strain with red fluorescent proteins (PLK/RED)]. However, in contrast to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 53 publications
6
74
0
Order By: Relevance
“…Results obtained are consistent with similar GBP1 recruitment to Tg-containing vacuoles and phagosomes (Qin et al, 2017;Shydlovskyi et al, 2017;Fisch et al, 2019a). Our single-cell assays conclusively reveal that GBP1 decorates two distinct intracellular populations of Tg within the same cell -those formed by host-mediated phagocytosis or those formed by Tg invasion.…”
Section: Discussionsupporting
confidence: 87%
“…Results obtained are consistent with similar GBP1 recruitment to Tg-containing vacuoles and phagosomes (Qin et al, 2017;Shydlovskyi et al, 2017;Fisch et al, 2019a). Our single-cell assays conclusively reveal that GBP1 decorates two distinct intracellular populations of Tg within the same cell -those formed by host-mediated phagocytosis or those formed by Tg invasion.…”
Section: Discussionsupporting
confidence: 87%
“…Recent findings show that, in mesenchymal stromal cells, hGBP1 localizes to the PCV membrane and inhibits parasite replication. This antimicrobial effect was, however, not observed for hGBP2 or hGBP5 . A different study performed in A549 lung epithelial cells suggested that hGBP1 does not associate with the T. gondii PCV .…”
Section: Introductionmentioning
confidence: 78%
“…This antimicrobial effect was, however, not observed for hGBP2 or hGBP5. 29 A different study performed in A549 lung epithelial cells suggested that hGBP1 does not associate with the T. gondii PCV. 30 Furthermore, in IFN-stimulated human fibroblasts T. gondii replication is controlled independently of hGBP1 and hGBP2, 31 and in HeLa cells, parasite growth is restricted by noncanonical autophagy.…”
Section: Gbps In the Defense Against Protozoa And Virusesmentioning
confidence: 97%
“…To counter the host defense mechanisms, Toxoplasma secretes ROP and GRA effector proteins into the host cell from organelles called rhoptries and dense granules, respectively. In both murine and human cells, the type II strain is more susceptible to IFNγ-mediated growth inhibition than the type I strain Haldar et al, 2015;Qin et al, 2017;Selleck et al, 2015). Resistance of type I strains in murine cells is determined primarily by polymorphic ROP5 and ROP18, which, together with ROP17 and GRA7, cooperatively block IRG and GBP loading on the PVM and subsequent events (Behnke et al, 2015;Etheridge et al, 2014;Fleckenstein et al, 2012;Haldar et al, 2015;Niedelman et al, 2012;Steinfeldt et al, 2010;Khaminets et al, 2010).…”
Section: Introductionmentioning
confidence: 99%